Strategic Human Resource Management and Firm Performance: The Mediating Role of Entrepreneurial Orientation - Zehir, Cemal; Gurol, Yonca; Karaboga, Tugba; Kole, Mahmut (ELSEVIER SCIENCE BV, 2016)
With the emergence of strategy literature both strategic aspect of human resource management and entrepreneurial activities in the organizations have been among the most remarkable subjects of research papers. In the literature the effect of strategic human resource management (SHRM) on firm performance has been extensively examined. The latest papers started to extensively investigate the effects of third variables in this relationship. Also, in recent years some researchers have studied and shown significant interactions between entrepreneurial orientation (EO) and human resource practices. In this study we focus on the important role of entrepreneurial orientation on the relationship between SHRM and firm performance. For this purpose a questionnaire was prepared and data were collected from the firms that operate in different industries in Istanbul. The collected data from questionnaires were analyzed with SPSS and AMOS software programs. Analyses results indicated that entrepreneurial orientation mediated the relationship between strategic human resource management and firm performance (both financial performance and employee performance). (C) 2016 The Authors. Published by Elsevier Ltd.
Keywords: Strategic human resource management; Entrepreneurial Orientation; Firm performance; ORGANIZATIONAL PERFORMANCE; BUSINESS PERFORMANCE; CORPORATE ENTREPRENEURSHIP; LINKING; IMPACT; CONSTRUCT; SYSTEMS; TQM; Business & Economics